Interaction miRNA miR-1273 family with mRNA genes regulating cell cycle and apoptosis (Experimental biology, 2015)
It was shown that genes involved in cell cycle regulation and apoptosis, are targets for the miR-1273 family. ATM,TP53 and VHL genes regulate the cell cycle and apoptosis and their mRNA have binding sites with miR-1273 family.CLSPN, MDM2, NF2, TRIM13 and LZTS1 genes proteins involved in cell cycle regulation and their mRNA are alsotargets for the majority of the studied miRNA. SPN, CASP, STK4 and DFFB genes participate in the regulation ofapoptosis and they are targets for miR-1273 family. Studied miRNA under the appropriate concentrations can greatlyaffect the expression of genes involved in cell cycle regulation and apoptosis.
Keywords: miRNA; gene; apoptosis; cell cycle; cancer